"Surviving not thriving": experiences of health among young people with a lived experience in out-of-home care. Issue 1 (31st December 2020) - Smales, Madelaine; Savaglio, Melissa; Morris, Heather; Bruce, Lauren; Skouteris, Helen; Green (nee Cox), Rachael
ABSTRACT: Children in care (CiC) experience poorer health outcomes than their same-aged peers without an experience of care. Despite growing recognition of the importance of listening to the voices of children and young people (YP), to date, the voices of CiC are not well represented in research examining their health. This study aimed to explore the experiences and perceptions of health among YP who have previously lived in care. A co-design approach was used to inform the research methodology by engaging YP with a lived experience in cooperative discussions. Ten YP participated in one-on-one semi-structured interviews and thematic analysis was used to analyse the data. The current findings highlight that YP consistently felt their health needs were not adequately met while in care, nor did they feel listened to, understood, or educated about health-related matters. This unique insight into the challenges they experienced in care offers realistic guidance for change.